Biological cyanide removal from industrial wastewater by applying membrane bioreactors. Issue 11 (6th July 2020) - Lintzos, Loukas; Koumaki, Elena; Mendrinou, Panagiota; Chatzikonstantinou, Kostas; Tzamtzis, Nikolaos; Malamis, Simos
Abstract: BACKGROUND: This work investigates whether the membrane bioreactor (MBR) process can effectively treat industrial wastewater containing high cyanide concentrations; cyanide may inhibit the biological processes, rendering such processes inadequate. In this work, the changes in process performance and microbial activity under gradually increased free cyanide (CN − ) concentrations (1, 3 and 10 mgCN − L −1 ) were investigated in two pilot‐scale MBR configurations. The MBR systems consisted of two parallel operating lines: a single aerobic (MBR1 ) and an aerobic/anoxic (MBR2 ). RESULTS: Cyanide removal was not adversely affected by the increase in cyanide concentration since removals up to 90% were obtained. Despite the inhibition that occurred, ammonia and organic carbon removal efficiency did not decrease, even at the highest cyanide concentration of 10 mgCN − L −1, and it remained high (>95%) in both systems. Nitrification (sAUR) was inhibited by 35%, 54%, and 64% in MBR1 and by 16%, 25%, and 36% in MBR2, with the addition of 1, 3, and 10 mgCN − L −1, respectively. The aerobic respiration (sOUR) was inhibited considerably less with an inhibition of 19%, 37%, and 45% in MBR1 and 9%, 16%, and 21% in MBR2 . The biomass maintained under both aerobic and anoxic conditions (MBR2 ) was more tolerant to cyanide compared to the biomass that was acclimated under only aerobic conditions (MBR1 ). CONCLUSION: At high cyanide load conditions, the MBR systems showed satisfactory removal of both cyanide and conventional pollutants despite the inhibition observed, indicating that MBR systems can successfully respond to the treatment of industrial wastewater that is heavily contaminated with cyanide. © 2020 Society of Chemical Industry